Optical NDT of composite materials - Sim, Wayne Ming Hui (2015)
B338: Optical NDT of composite materials investigates the usage of non-destructive testing(NDT) method as a means to detect defects within composite materials. Shearography is one of the non-destructive testing methods being employed to detect defects in composites. It employs coherent light to measure the displacement derivatives caused by subsurface defects. In order to detect these defects, deformations or strains in the materials have to be created. These deformations are achieved through various methods such as thermal, vibration or physical loadings. These deformations are than captured by the shearography system through the use of CCD cameras. The images captured would be processed by software algorithms and thus giving us useful information on the subsurface defects in the materials. Composite materials are the combination of two or more materials with different physical or chemical properties. The combined materials give us the properties we desire. However defects in these composites can be difficult to measure and detect with conventional NDT techniques due to non-homogeneity of the combined materials. Shearography is able to detect these defects in the composites as well as giving a faster response time as compared to the other NDT techniques such as ultrasonic. Shearography is targeted toward the aerospace industry where competition is high and speed is of essence. Therefore, high-speed inspection systems are necessary. However, since Shearography is a comparatively new technique, more research has to be conducted to explore the extent of this technique. In this paper, the author will investigate the use of the shearography system to inspect manufactured defects in composites. The results of the investigation will be cataloged for further studies.